Private Health Investments under Competing Risks: Evidence from Malaria Control in Senegal - Pauline Rossi; Paola Villar (Tinbergen Institute, 2017)
This study exploits the introduction of high subsidies for anti-malaria products in Senegal in 2009 to investigate if malaria prevents parents to invest in child health. Building upon the seminal paper of Dowetal. (1999), we develop a simple model of health investments under competing mortality risks, in which people allocate expenses to equalize lifetime across all causes of death. We predict that private health investments to fight malaria as well as other diseases should increase in response to anti-malaria public interventions. To test this prediction, we use original panel data from a Senegalese household survey combined with geographical information on malaria prevalence. Our strategy is to compare the evolution of child health expenditures before and after anti-malaria interventions, between malarious and non-malarious regions of Senegal. We find that health expenditures in malarious regions catch up with non-malarious regions, at the extensive and intensive margins, and both in level and in composition. The same result holds for parental health-seeking behaviour in case of other diseases like diarrhea. We provide evidence that these patterns cannot be explained by differential trends in total income or access to health care or child morbidity between malarious and non-malarious regions. Our results suggest that behavioural responses to anti-malaria campaigns magnify their impact on all-cause mortality for children.
Keywords: D1; H51; I1; O15; 330; Health; investments; Malaria; Africa